Managing Gallstone during Pregnancy: Tatalaksana Batu Empedu pada Kehamilan - Toar JM Lalisang; Fransisca J Siahaya (Indonesian Socety of Obstetrics and Gynecology, 2013)
Transient physiological changes in the biliary system during pregnancy increased the risk of gallbladder diseases. Nonoperative management of symptomatic cholelithiasis increases the risk of complications of biliary lithiasis, such as cholecystitis and empyema, while obstruction common bile duct stones with or without cholangitisb and biliary pancreatitis raise maternal mortality. Delay in definitive surgical treatment of biliary diseases during pregnancy increases the likelihood acute biliary pancreatitis which impact on preterm delivery until fetal lost. Laparoscopic cholesystectomy during pregnancy has advantages for the mother in that it speeds up her recovery, giving her less pain and facilitated natural birth without a cesarean section. On the fetus side, laparoscopic cholecystectomy is safe since it does not induce preterm delivery or abortion. Identification of gallbladder stone during pregnancy warrant a preventive laparoscopic cholesystectomy or endoscopic CBD exploration, both of which promise good outcomes. Keywords: adult choledochal cyst, biliary cyst, biliary dilatation, mixed type